1986
DOI: 10.1007/bf00181245
|View full text |Cite
|
Sign up to set email alerts
|

An observational analysis of the effect of the selective kappa opioid agonist, U-50,488H, on feeding and related behaviours in the rat

Abstract: The behaviour of partially pre-satiated rats consuming a sweet palatable food and treated with either vehicle or the specific kappa receptor agonist U-50,488H (0.1-3 mg/kg) was recorded on videotape. Analysis revealed that the hyperphagia induced by the kappa agonist (0.3-3 mg/kg) resulted from an increase in the duration of feeding and not from an increase in the local rate of eating. The increase in duration was due, in turn, to a greater frequency of bouts of feeding. The kappa agonist also increased the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…In adult rats the ~c-agonist ketocyclazocine has been shown to increase locomotor activity one hour after injection (Iwamoto 1981) and the mixed agonistantagonist bremazocine has been reported to induce ~c-mediated backward walking over a 2-h test (Shearman and Stenfors 1986). High doses of the more selective ~c-agonists U50,488H and PD 117,302, however, produce behavioural depression in mature rats and mice (Von Voigtlander et al 1983;Hayes et al 1985;Ukai and Kameyama 1985;Jackson and Cooper 1986;Leighton et al 1987) up to I h after dosing. A low dose of U50,488H (0.1 mg/kg) increases grooming behaviour in fully-grown rats whilst reducing rearing and having no effect on forward locomotion (Jackson and Cooper 1986).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In adult rats the ~c-agonist ketocyclazocine has been shown to increase locomotor activity one hour after injection (Iwamoto 1981) and the mixed agonistantagonist bremazocine has been reported to induce ~c-mediated backward walking over a 2-h test (Shearman and Stenfors 1986). High doses of the more selective ~c-agonists U50,488H and PD 117,302, however, produce behavioural depression in mature rats and mice (Von Voigtlander et al 1983;Hayes et al 1985;Ukai and Kameyama 1985;Jackson and Cooper 1986;Leighton et al 1987) up to I h after dosing. A low dose of U50,488H (0.1 mg/kg) increases grooming behaviour in fully-grown rats whilst reducing rearing and having no effect on forward locomotion (Jackson and Cooper 1986).…”
Section: Discussionmentioning
confidence: 95%
“…High doses of the more selective ~c-agonists U50,488H and PD 117,302, however, produce behavioural depression in mature rats and mice (Von Voigtlander et al 1983;Hayes et al 1985;Ukai and Kameyama 1985;Jackson and Cooper 1986;Leighton et al 1987) up to I h after dosing. A low dose of U50,488H (0.1 mg/kg) increases grooming behaviour in fully-grown rats whilst reducing rearing and having no effect on forward locomotion (Jackson and Cooper 1986). Similar increases in grooming have been observed after central administration of dynorphin (Katz et al 1980b;Zwiers et al 1981), the putative endogenous ligand for ~c-receptors (Chavkin et al 1982), although there was no indication of stimulatory effects of ~c-agonists on this behaviour in neonatal rats.…”
Section: Discussionmentioning
confidence: 96%
“…The j opioid agonist U-50, 488H (Sigma, Poole, UK) (trans-3,4-dichloro-N-methyl-N-[2-(1-pyrrolidinyl)-cyclohexyl]-benzeneacetamide methanesulfonate) was dissolved in distilled water and injected SC, 30 min before testing. The doses were 0.3, 1, and 3 mg / kg, and have been shown to enhance intake in non-deprived rats (Jackson and Cooper 1986). All drugs were injected in a volume of 1 ml / kg.…”
Section: Drugsmentioning
confidence: 98%
“…(1983) obtained dose-related decreases in activity counts at doses of 5 and 10 mg/kg; thus it is likely that the doses employed in this study were not high enough to observe inhibitory effects on forward locomotion. In our previous work with this compound, we have looked at effects of U-50,488H on the same behaviours, using a dose range which includes those employed here (Jackson and Cooper 1986). During the course of this work, we noted a stimulation of grooming behaviour at a dose of 0.1 mg/kg U-50,488H.…”
Section: Discussionmentioning
confidence: 99%
“…It does not necessarily follow that reductions in locomotor activity are accompanied by similar changes in grooming and/or rearing. Few reports have addressed the question of kappa agonist effects on these discrete behaviours, but in one observational study, the selective agonist U-50,488H was found to either stimulate or suppress grooming behaviour in rats, depending on the dose employed (Jackson and Cooper 1986).…”
mentioning
confidence: 99%